Identifying Shariah Governance and Construction Procurement System of Property Development Under Islamic Johor Corporation - Ahmad Sarkawi , Azila; Aripin, Srazali (International Journal of Psychosocial Rehabilitation, 2020)
Islamic Johor Corporation or in Malay language, Perbadanan Islam Johor (PIJ) is a corporation established in 1976 to advance the economy of Muslims in Johor. The corporation embarks in property developments that lead to the formation of PIJ Holdings in 1995. As such, the objective of this study is to recognize the shariah governance and construction procurement system from the practice of PIJ’s property development. In the deficiency of standard shariah governance framework for property development services, the study referred to the selected guiding principles from an international standard of Islamic Financial Services Board (IFSB), Accounting and Auditing Organisation for Islamic Financial Institutions (AAOIFI) and Shariah Governance Framework for Bank Negara Malaysia. In doing so, the paper articulates the set-up of PIJ and discusses the steps of its construction procurement process from the initiation of the project until the management of risk. The study employed qualitative research methods of content analysis, case study and an interview to validate the findings. The study found that there is a synergy between the religious authorities and PIJ in its set-up, acts as a check and balance to the practice of its property development. Moreover, its operational practices help to identify the Islamic procurement element for instances the employment of project financing via Islamic banking and takaful. For other procurement activities, it can be said that PIJ is acknowledging the conventional methods so long it does not contradict to Islam. This identification is significant to promote PIJ as a catalyst to shariah-compliant property development.